IMPLEMENTASI PROFESIONALISME GURU DALAM MEMOTIVASI BELAJAR SISWA DI SEKOLAH DASAR - Vitalis Djarot Sumarwoto (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2011)
Professionalism seems to develop at all sectors in Indonesia today. Many efforts have been undertaken by the decision makers of education to pursue it. Among other efforts done by the authorities is the professional teacher certification. The implementation of professional teacher certification has basically referred to the Law No. 19, year 2005, on the National Education Standard; and the Governmental Regulation No. 74 year 2008 on Teachers, which suggest that teachers are obliged to have relevant academic qualification, competence and certification of educator. The objective of those regulations is only very prestigious i.e. to make them enhance qualified working experience within a certain interval of time. Hopefully, after they are certified professionally, they are able to encourage students to learn, especially for elementary students